KOMUNIKASI INTERPERSONAL SEBAGAI FAKTOR KEPUTUSAN TETAP BEKERJA DI SEKTOR PERTAMBANGAN (STUDI KASUS DI KOTA SAMARINDA) - Hayati, Afita Nur; Safitri, Ade Irma; Utami, Anindya Putri; Nofianti, Ayu; Maharani, Erviana Arya; Yuli, Erza; Magfirah, Riska; Ramadhan, Sinar; Muzizah, Siti; Nurhidayat, Qanithah (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Samarinda is a coal-producing city and is included in the mining area. It has a very large population, so mining workers are dominant in the province of East Kalimantan. This study uses quantitative and descriptive analysis methods. Individuals are rational actors, where each individual must have the nature of wanting to act to be able to compare the results and benefits of the things that are available. Individual decisions become the main thing when doing work. Ability and motivation must come before labor in carrying out work. In the problem of job satisfaction, there are factors that can motivate workers, including salary, working conditions, policies, international relations, and the quality of supervisors